Ab-Initio Investigation into the Physical Characteristics of CuInSe2 and CuInTe2 Compounds - Yousra Megdoud; Yamina Benkrima; Redhe Meneceur; Latifa Tairi; Abdelghani Lakel; Sebti Ghemid; Hocine Meradji (East European Journal of Physics, 2023)
In this study, an analysis of chalcopyrite compounds CuInTe2 and CuInTe2 is presented, with a focus on their electronic, structural, optical, and thermal properties. The full-potential linearized augmented plane wave (FP-LAPW) method is employed for the investigation of these properties, based on a first-principles approach rooted in density functional theory (DFT). Two distinct approximations for the exchange and correlation potential, namely the WC-GGA and mBJ-GGA approximations, are considered in our calculations to ensure a robust and accurate examination of the materials under scrutiny. The findings obtained closely align with previously established theoretical and experimental data, thereby validating the reliability of our computational methodology. It is noteworthy that a novel dimension is introduced by this study, as the influence of both pressure and temperature on the thermal parameters of CuInTe2 and CuInTe2 compounds is explored. This facet of the research is distinguished by its innovative nature, as there is no prior record, to the best of our knowledge, of a similar analysis in the existing literature. The thermal properties are deemed of paramount significance, particularly in the context of crystal growth process optimization and the prediction of performance under extreme thermodynamic conditions.